The impact of lesson study professional development on teacher self-efficacy and outcome expectancy - Nauerth, Deborah Anne (Kansas State University, 2015)
The purpose of this mixed methods case study was to examine the impact of lesson study professional development on teacher self-efficacy and outcome expectancy using Bandura’s Social Cognitive Theory as a framework (1977). The focus of this lesson study was implementing Common Core State Standards for mathematics. Thirteen K-6 teachers participated in the lesson study professional development, completed a pre/post Mathematics Teaching Efficacy and Expectancy Beliefs Inventory (MTEEBI) and completed ongoing journaling prompts while the researcher conducted observations throughout the process. Qualitative and quantitative data gathered in this research indicated the lesson study professional development had a positive impact on both self-efficacy and outcome expectancy of the teacher participants. Though the teachers possessed a satisfactory level of self-efficacy and outcome expectancy at the onset of the study, a measurable gain was evident. Comparison of the pre and post MTEEBI surveys, through statistical analysis using a Paired-Samples t-test, indicated a significant positive change in both self-efficacy and outcome expectancy scores. Though growth for both constructs was significant at the .05 level of probability, self-efficacy growth was greater than outcome expectancy. This finding is supported in historical research of the challenge of yielding outcome expectancy growth. The qualitative analysis of observations and journal prompts corroborated the MTEEBI results, indicating a majority of the teachers’ self-efficacy and outcome expectancy beliefs were positively impacted by the lesson study professional development. Bandura’s four sources of efficacy (mastery experiences, modeling, verbal/social persuasion, physiological responses) positively impacted personal self-efficacy, while three of the four sources (mastery experiences, modeling, physiological responses) impacted outcome expectancy. Qualitative data indicated mastery experiences were most critical for both constructs. Lesson study professional development is a natural catalyst for addressing Bandura’s four sources of efficacy and thus building self-efficacy and outcome expectancy. Given the demands of rigorous educational reform, lesson study professional development is a promising approach to positively impact teacher self-efficacy and outcome expectancy, through engaging Bandura’s four sources of efficacy to develop and strengthen these beliefs. Therefore lesson study ought to be a more frequent component of teacher professional development and teacher preparation.
Keywords: Lesson study; Social Cognitive Theory; Self-efficacy; Outcome Expectancy; MTEEBI; Mathematics; Curriculum Development (0727); Elementary Education (0524); Teacher Education (0530)